The Islamic state in Britain radicalization and resilience in an activist network - Kenney, Michael 1967- (Structural analysis in the social sciences, 2018)
"Drawing on extensive field research with activists on the streets of London, Michael Kenney provides the first ethnographic study of a European network implicated in terrorist attacks and sending fighters to the Islamic State. For over twenty years, al-Muhajiroun (Arabic for 'the Emigrants') strived to create an Islamic state in Britain through high-risk activism. A number of Emigrants engaged in violence, while others joined the Islamic State in Iraq and Syria. Kenney explains why young Britons joined the Emigrants, how they radicalized and adapted their activism, and why many of them eventually left. Through an innovative mix of ethnography and network analysis, Kenney explains the structure and processes behind this outlawed network and explores its remarkable resilience. What emerges is a complex, nuanced portrait that demystifies the Emigrants while challenging conventional wisdom on radicalization and countering violent extremism"...